Real estate market trends and the desirability of vertical housing in Monterrey, Nuevo León (GEON Journal (Management, Organizations and Business), 2024)
The change in public policies in the municipality of Monterrey, Nuevo Leon, since 2000, has led to the modification of neighborhoods near the center of the city. Part of this modification is due to the redensification characteristics applied in the new construction regulations, which has caused, for a little more than twenty years, the vertical growth of the city through real estate and mixed-use projects, with rental and sales costs that exceed those of a similar residential house. Determine the behavior and trends of the apartment real estate market in Monterrey, Mexico, during the pre- and post-pandemic 2020. This article is based on information obtained from a database that was compiled from transactions located in the SAX system and various specialized market studies. This information is analyzed to define the trends of the municipal real estate market by means of a correlation analysis for the characteristics of the environment and a multiple linear regression process for the variables of the study subjects. As part of the contribution of this research is the identification of the areas with the highest capital gains, the areas with the highest growth, as well as the way in which the apartment market has been changing according to the characteristics of the properties and the needs of their residents. It is generated from determining the parameters that influence the cost of vertical housing, which can benefit the population thanks to the approximation of the information provided and analyzed, in order to see the effects of public policies proposed by the municipality of Monterrey and give guidelines for future research that can be derived from this study with the purpose of contributing to the real estate market. This article presents a method and a set of tools that allow us to analyze the evolution of different indicators -here exposed- and show the behavior of the real estate market of apartments in downtown Monterrey in a period of time that goes from 2018 to 2022. This can be applied for other indicators, variables and in other study contexts.
Keywords: Real estate market; apartments; desirability; redensification; real estate projection